2019
DOI: 10.3390/nu11020266
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake and Associated Factors in Long-Term Care Homes in Southeast Spain

Abstract: Diet is a key modifiable factor in the management of malnutrition and age-related diseases such as sarcopenia, an important issue in long-term care homes. The objectives of this study were to evaluate the dietary intake of residents, define dietary patterns, and analyze their association with sex, diet texture, nutritional status, and the presence of sarcopenia. Intake was assessed by the precise weighing method, dietary patterns were defined a posteriori by cluster analysis, and nutritional status and sarcope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
(56 reference statements)
3
26
3
1
Order By: Relevance
“…Engelheart et al observed that there was no correlation between nutritional status and energy or protein intake among older people living at home or in a nursing home [4]. Thus, assessing energy and protein intake might be a more sensitive assessment than a mere MNA screening tool to detect those at risk of developing malnutrition [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Engelheart et al observed that there was no correlation between nutritional status and energy or protein intake among older people living at home or in a nursing home [4]. Thus, assessing energy and protein intake might be a more sensitive assessment than a mere MNA screening tool to detect those at risk of developing malnutrition [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the prevalence of sarcopenia and frailty may be as high as 50 to 60% in older adults at residential aged care facilities owing largely to low levels of physical activity, prolonged sedentary behaviour and malnutrition, particularly inadequate protein intake. 9,40 Current clinical guidelines for older adults who are malnourished or at risk of malnutrition because they have acute or chronic illness recommend a dietary protein intake of 1.2-1.5 g protein/kg body weight/day. 24,41 Despite these recommendations, findings from several randomised trials have reported mixed findings regarding the effects of protein supplementation on measures of muscle mass, strength and/or physical function in these populations.…”
Section: Supplementation In Residential Aged Care Residents and Frailmentioning
confidence: 99%
“…5,6 This predisposes an older adult to sarcopenia, a skeletal muscle wasting disease with an ICD-10-AM code that was first recognised by Irwin Rosenberg in 1988. 7 Sarcopenia affects between 10-40% of community-dwelling older adults (depending on the definition applied), 8 while among nursing home residents and acutely hospitalised patients it has been reported that the prevalence may be up to 63% 9 and 40%, 10 respectively. While SMM loss is adversely associated with fragility fractures (including hip fractures), mobility impairment, increased falls risk and premature mortality in community-dwelling older adults, 11,12 there is a growing body of evidence linking the loss of SMM to most common chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to nutritional status, previous studies have found low energy intake to be associated with frailty among community-living older people (11,12). Although studies investigating the associations between frailty and energy intake among nursing home residents are scarce, it is known that energy intake is often inadequate in nursing homes (13)(14)(15). In their study, Jyväkorpi et al found that even older residents with good nutritional status had inadequate energy intake (13).…”
Section: Introductionmentioning
confidence: 95%